2022
DOI: 10.1051/0004-6361/202142843
|View full text |Cite
|
Sign up to set email alerts
|

Starbursts with suppressed velocity dispersion revealed in a forming cluster at z  =  2.51

Abstract: One of the most prominent features of galaxy clusters is the presence of a dominant population of massive ellipticals in their cores. Stellar archaeology suggests that these gigantic beasts assembled most of their stars in the early Universe via starbursts. However, the role of dense environments and their detailed physical mechanisms in triggering starburst activities remain unknown. Here we report spatially resolved Atacama Large Millimeter/submillimeter Array (ALMA) observations of the CO J = 3−2 emission l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 115 publications
0
11
0
Order By: Relevance
“…While this ensures that we are able to detect most of the SF members above this mass limit, some of the most obscured ones may still be missed. We hence complemented this sample of Hα emitters with our previously confirmed cluster members based on CO(1-0) (Wang et al 2016(Wang et al , 2018 and CO(3-2) (Xiao et al 2022) observations.…”
Section: Data: Member Galaxies Selection and Hst Imagingmentioning
confidence: 95%
“…While this ensures that we are able to detect most of the SF members above this mass limit, some of the most obscured ones may still be missed. We hence complemented this sample of Hα emitters with our previously confirmed cluster members based on CO(1-0) (Wang et al 2016(Wang et al , 2018 and CO(3-2) (Xiao et al 2022) observations.…”
Section: Data: Member Galaxies Selection and Hst Imagingmentioning
confidence: 95%
“…The median r 31 value is comparable to that of other highredshift galaxies reported in the literature. In the VLASPECS survey (Riechers et al 2020), the median r 31 for MS galaxies at z = 2-3 is 0.84 ± 0.26; Xiao et al (2022) reported an r 31 of 0.8 for two starburst galaxies in a z = 2.5 protocluster, and Sharon et al (2016) found r 31 = 0.78 ± 0.27 for a sample of lensed and unlensed SMGs at z ∼ 2. Our value for r 31 is higher than the ratio found by Ivison et al (2011), 0.55 ± 0.05, for SMGs at z = 2.2-2.5, and consistent with 0.63 ± 0.12 from Birkin et al (2021).…”
Section: Co Spectral Line Energy Distributions and Line Ratiosmentioning
confidence: 99%
“…Our knowledge of the cold molecular gas content in nonlensed systems comes from targeted studies (Carilli et al 2010;Riechers et al 2011bRiechers et al , 2011aIvison et al 2011;Sharon et al 2016;Huynh et al 2017;Kaasinen et al 2019;Leung et al 2019;Frias Castillo et al 2022;Xiao et al 2022). While valuable, carrying out a systematic study of a statistically significant sample of CO(1-0) emission of high-redshift galaxies has been hampered by the rather heterogeneous selection criteria applied in the different studies.…”
Section: Introductionmentioning
confidence: 99%
“…The median r 31 value is comparable to that of other highredshift galaxies reported in the literature. In the VLASPECS survey (Riechers et al 2020), the median r 31 for MS galaxies at z = 2-3 is 0.84±0.26; Xiao et al (2022) We include literature values of unlensed SMGs and SFGs with CO(1-0) detections. We find no significant correlation for these variables with either ratio.…”
Section: Co Spectral Line Energy Distributions and Line Ratiosmentioning
confidence: 99%
“…Our knowledge of the cold molecular gas content in nonlensed systems comes from targeted studies (Carilli et al 2010;Ivison et al 2011;Riechers et al 2011a,b;Sharon et al 2016;Huynh et al 2017;Kaasinen et al 2019;Leung et al 2019;Frias Castillo et al 2022;Xiao et al 2022). While valuable, carrying out a systematic study of a statistically significant sample of CO(1-0) emission of high-redshift galaxies has been hampered by the rather heterogeneous selection criteria applied in the different studies.…”
Section: Introductionmentioning
confidence: 99%